(untitled) (Pedagogical Horizons, 2024)
The research project Ko:KiS (duration: 02/2021-10/2022) aims to make visible the current structures and framework conditions regarding the cooperation of kindergarten and school in the province of Upper Austria and to formulate structural, legal and pedagogical conclusions with the active participation of all stakeholders (elementary and primary educators, parents, children, educational policy and pedagogical decision-makers). The first result of an online survey of more than 500 elementary and primary educators shows that the willingness and commitment to collaboration among the respondents tends to be high and is also pushed by superiors. More than half of the respondents are satisfied with the standardized developmental screenings and tests that have already been implemented. At the same time, it seems paradoxical that 69% of the teachers and 93% of the elementary teachers are not convinced that school readiness can be assessed selectively on one day.